Tympanoplasty following Blast Injury. (4th July 2017) - Keller, Matthew; Sload, Ryan; Wilson, Justin; Greene, Howard; Han, Peggy; Wise, Sean
Abstract : Objectives: To assess outcomes following tympanoplasty for blast‐induced tympanic membrane perforations in a military population. Study Design: Case series with chart review. Setting: Tertiary care medical centers. Subjects and Methods: Military personnel (N = 254) undergoing tympanoplasty for blast‐related tympanic membrane perforations sustained between April 2005 and July 2014 were identified from the Expeditionary Medical Encounter Database. Descriptive statistics were obtained regarding demographics, primary and revision surgery success rates, hearing status pre‐ and postsurgery, and frequency of ossicular reconstruction. Rates of successful perforation closure were assessed against perforation size and character (central vs marginal) and time to surgery. Rates and types of complications were additionally explored. Results: There were a total of 352 operations among 254 subjects, with an 82.1% rate of successful closure following primary surgery. For successful primary tympanoplasty, the mean improvement in pure tone average was 11.7 ± 12.1 dB. Ossiculoplasty was performed in 9.1% (32 of 352) of cases. There was no significant relationship between successful perforation closure and perforation size, perforation character, or time between injury and surgery. Cholesteatoma complicated 4.3% (15 of 352) of cases. A significant relationship was identified between risk of cholesteatoma development and increasing perforation size and marginal perforations. Conclusion: Tympanoplasty success rates for blast‐induced tympanic membrane perforations are lower than for other common injury mechanisms. Due to appreciable rates of postoperative cholesteatoma development, close clinical surveillance is recommended.